Development and Testing of Solar Powered Evaporative Air-Cooling System with an Improved Performance. Issue 1 (31st December 2023) - Mekonen, Tadelle N.; Delele, Mulugeta A.; Molla, Sissay W.
Abstract: This study proposes a new active direct evaporative cooling system that uses a bundle of cotton fibers as an evaporating surface and activated carbon as a moisture adsorbent. A two-stage evaporative cooling experimental setup consisting of an activated carbon adsorbent in between the cooling pad was designed, fabricated, and tested at Bahir Dar, Ethiopia. The fiber bundle (pad 1) was wetted with water and ambient air was forced through it using a fan then the air that exiting from pad 1 was forced through a bulk of activated carbon (moisture adsorbent), and then the air from the adsorbent passed through the second wetted fiber bundle (pad 2). The energy source for the fan and pump was the solar photovoltaic energy system. The average temperature drop of the cooler without the moisture adsorber was 9.33°C and with the inclusion of the moisture, the adsorber gave an additional temperature drop of 1.5°C to 4.95°C. During the hot dry season, the average relative humidity of the ambient air, pad 1 outlet, adsorbent outlet, and pad 2 outlets were 28.26%, 76.12%, 55%, and 88.2% respectively. The cooler with moisture adsorbent had a cooling capacity of 3653 W, an effectiveness of 94.25%, and a COP of 52.2. The developed solar evaporative cooling system can provide energy-efficient, sustainable, affordable cold air for different applications. The cooler could be used by small-scale farmers, wholesalers, and retailers for the cooling and storage of horticultural products to reduce the postharvest loss in fresh produces.